Manutenção produtiva total: o caso da Eletronorte - Palmeira, Jorge Nassar (2001)
The continuous search of the increase of the productivity has been facilitating the growing diffusion of modern and advanced technologies, that open new ways for the renovation of the industrial productive process, as well as, to the appearance of modern administration systems that establish ways in direction to the democratization of the social relationships in the organizations. Accompanying that tendency and, motivated by the competitive characteristic of the market of electric energy, Eletronorte, adopted the Total Productive Maintenance - TPM, of japanese origin, as the system of administration of its productive process. This dissertation has as objective, to analyze the methodological content of the Total Productive Maintenance, showing its significance and its reach in the Regional of Transmission of Mato Grosso, adopting the post fordism, as comparison paradigm. The whole study and analysis had as focus the offices of the company and the Substation of Coxipó, placed in the city of Cuiabá, as well as the Substations of Rondonópolis and Sinop, placed in cities with the same name. The offices and the substations are geographically located in the state of Mato Grosso, and under the responsibility of the Regional of Transmission of Mato Grosso, of the Centrais Elétricas do Norte do Brasil SA - Eletronorte. The work method was of qualitative orientation and of case study, through a research of applied nature. The research was accomplished with explanatory and exploratory objectives. They were used as instruments of collection of data the analysis of documents, interviews, and application of questionnaires. The data collected through documents and of the application of questionnaires they were compiled and analyzed. The results of the interviews had for objective to confirm the consistency of the collected data. The obtained results demonstrate increases of productivity of the order of 40%, and reduction of the costs of up to 29%. The study still demonstrated, that TPM provoked significant impacts in the practices you work, denoting the presence of an action managerial dialógica. It was still characterized that the transference of TPM will depend in that context the administration system will be applied, because if this is here different from it studied, there won't be transference warranties.